2015
DOI: 10.1159/000374119
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Antidepressant Medication before and after the Diagnosis of Amyotrophic Lateral Sclerosis: A Population-Based Cohort Study

Abstract: Background: The prevalent use of antidepressants (ATDs) in patients with Amyotrophic Lateral Sclerosis (ALS) varies across cross-sectional and clinic-based published studies. This population-based cohort study assesses the real-world prevalence of the use of ATDs, its trajectory and the association of incident use with clinical characteristics. Methods: All patients with incident ALS in the Friuli Venezia Giulia region, Italy, from 2002 to 2009, were identified through multiple sources including health databas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 37 publications
1
8
0
1
Order By: Relevance
“…Nonetheless, this finding appears consistent with the results of a recent study on ALS patients, which observed, more than 1 year before ALS diagnosis, a 2-fold prevalence ratio of antidepressant use, compared to the general population [31] . A narrative review on the relationship between exposure to antipsychotics and antidepressants, and ALS onset has hypothesized that these drugs may reduce the risk of developing ALS [15] .…”
Section: Discussionsupporting
confidence: 92%
“…Nonetheless, this finding appears consistent with the results of a recent study on ALS patients, which observed, more than 1 year before ALS diagnosis, a 2-fold prevalence ratio of antidepressant use, compared to the general population [31] . A narrative review on the relationship between exposure to antipsychotics and antidepressants, and ALS onset has hypothesized that these drugs may reduce the risk of developing ALS [15] .…”
Section: Discussionsupporting
confidence: 92%
“…23,24 Patients with ALS may be prescribed with antidepressants for reasons other than depression, such as excessive salivation where the anticholinergic side effect of antidepressants is desirable and emotional outbursts where the patients suddenly and without control cry or laugh. These possibilities likely explain the more pronounced risk increase for antidepressant use after ALS diagnosis, compared to depression diagnosis, as observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The aforementioned sources of data provide patient‐level information and have been used for research on use of medications before . For each hospitalization, the hospital registry records information on patient demographics, dates of admission and discharge, and one primary and up to five secondary discharge diagnoses coded according to the International Classification of Diseases version 9 (ICD‐9‐CM) coding system.…”
Section: Methodsmentioning
confidence: 99%